Technical Challenges in Microgrid (International Journal of Psychosocial Rehabilitation, 2020)
Capability of distributed generation system in grid connection system that allure researchers due to the economical electricity demand and also deal with the environmental problems as new arising technologies for maintaining and supplying reliable and efficient power, for making the reliable system of electricity a concept will be adopted that is micro grid which increasing appealing to customers, many of them will be located at the consumer's site in the future, but in this system face the serious difficulty that is control and protection, this places a load on the operations of network and there will be some technical limitations when a large number of distribution generations are installed. A microgrid is usually connected to an electrical distribution system that uses various technologies for generating distribution, such as photovoltaics, fuel cells, etc., in the energy storage devices, such as batteries, and a backup source, such as a diesel generator and grid source. Which is designed to provide effective heat and electricity delivery service by connecting distributed generation with a small area. This paper presents the review of technical challenges in microgrids and typical distributed technologies for generation in microgrids. It also studies its architecture, operation, control, protection, and transmission strategies, which are highlighted in this paper. In addition, it helps the researchers in visualizing an actual circumstance when we are making use of microgrids today and also provides perception into the possible involvement of future grids.